2013
DOI: 10.1038/nmat3647
|View full text |Cite
|
Sign up to set email alerts
|

A general approach to DNA-programmable atom equivalents

Abstract: Nanoparticles can be combined with nucleic acids to programme the formation of three-dimensional colloidal crystals where the particles' size, shape, composition and position can be independently controlled. However, the diversity of the types of material that can be used is limited by the lack of a general method for preparing the basic DNA-functionalized building blocks needed to bond nanoparticles of different chemical compositions into lattices in a controllable manner. Here we show that by coating nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
310
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 285 publications
(314 citation statements)
references
References 33 publications
4
310
0
Order By: Relevance
“…S3). These values are comparable to those achieved with similarly sized inorganic nanomaterials previously used in DNA-mediated crystallization schemes (12,29). Further characterization of each protein conjugate by dynamic light scattering (DLS) revealed increases in their hydrodynamic diameters after DNA functionalization from 11.7 or 12 nm to 24.3 and 25 nm for bovine and Cg catalases, respectively, which is consistent with the formation of a shell of oligonucleotides oriented radially from the protein cores ( Fig.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…S3). These values are comparable to those achieved with similarly sized inorganic nanomaterials previously used in DNA-mediated crystallization schemes (12,29). Further characterization of each protein conjugate by dynamic light scattering (DLS) revealed increases in their hydrodynamic diameters after DNA functionalization from 11.7 or 12 nm to 24.3 and 25 nm for bovine and Cg catalases, respectively, which is consistent with the formation of a shell of oligonucleotides oriented radially from the protein cores ( Fig.…”
Section: Resultssupporting
confidence: 84%
“…For aggregates containing only DNA-functionalized proteins, this transition results from dehybridization of double-stranded DNA into hyperchromatic single-stranded DNA upon dissociation of the aggregates, whereas for aggregates containing a mixture of DNAfunctionalized proteins and SNA-AuNP conjugates, the increase in the extinction is largely due to changes in the optical properties of the AuNPs. The melting temperatures and full-width at half-maximum (FWHM) values for these transitions were similar to those observed for SNA-NP conjugates with inorganic cores (12,29).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…At the colloidal scale, such interactions have a range that is much shorter than the size of the particles. The use of DNA labeling to control binding specificity was originally pioneered for assembling nanoparticles (14)(15)(16)(17) into infinite crystals (18)(19)(20)(21)(22)(23)(24), where recently it was demonstrated that with two species with differing particle radii and DNA linker length a zoo of different crystal morphologies can be created (25). Work at the colloidal scale has begun to bear fruit (13,17,(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…DNA-guided nanoparticle colloidal crystallization provides remarkable control over the assembly of nanoparticles into superlattices (9,10), enabling the deliberate tailoring of crystal symmetry (9), lattice constant (11), and particle composition (12). Furthermore, structures with geometrically well-defined 3D crystal habits (10), when locked into the solid state via silica embedding procedures (13), open up potential applications in the field of optics.…”
mentioning
confidence: 99%